Effect of Co-Culturing Neural Cells with MSCs on Spheroid Formation and Their Recovery After Cryopreservation - Vsevolodska, Svitlana; Ochenashko, Olha; Maiorova, Olha; Sukach, Oleksandr (Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(4):293